Molecularly imprinted polymeric sensings layers grafted from aryl diazonium‐modified surfaces for electroanalytical applications. A mini review1. (22nd April 2014) - Bakas, Idriss; Salmi, Zakaria; Gam‐Derouich, Sarra; Jouini, Mohamed; Lépinay, Sandrine; Carbonnier, Benjamin; Khlifi, Akila; Kalfat, Rafik; Geneste, Florence; Yagci, Yusuf; Chehimi, Mohamed M.; Abel, Marie‐Laure; et al.
<x xml:space="preserve">Abstract</x> We review our strategy to attach polymerization initiators to electrode surfaces by electroreduction of aryl diazonium salts. The 5 nm‐thick aryl layers efficiently initiate the growth of crosslinked polymer grafts prepared in the presence of template molecules. We address the important parameters in obtaining highly sensitive molecularly imprinted vinylic polymer layers grafted on working electrodes such as glassy carbon, gold and indium tin oxide. Square wave voltammetry is the preferred electroanalytical tool while the limit of detection (LOD) of analytes can be decreased down to subnanomolar detection by synthesizing ultrathin layers in the 20–30 nm thickness. Further improvement can be achieved with molecularly imprinted polymer layers with embedded gold nanoparticles. Rebinding solvent is demonstrated to be another important parameter for lowering LOD. This work highlights XPS as a unique surface sensitive technique for monitoring the chemical composition changes occurring at the electrode surface during the building of the high performance sensing layers as well as for evidencing the reversible complexation of the template molecule by the molecularly imprinted recognition sites. Copyright © 2014 John Wiley & Sons, Ltd.